The cost effectiveness of transesophageal echocardiography for pediatric cardiac surgery: a systematic review. Issue 7 (14th May 2016) - Levin, David N.; Taras, Jillian; Taylor, Katherine
Summary: Background: Intraoperative transesophageal echocardiography (ITEE) for pediatric cardiac surgery has been described as clinically efficacious and cost‐effective. There are a small number of publications supporting these claims. Aims: The objectives were to assess the quality of the research, the variability of results across studies and, if possible, to make a consensus statement based on the results. Methods: In March 2015, a systematic search of MEDLINE and MEDLINE In‐Process, EMBASE, and the National Health Service Economic Evaluation Database was performed. The search was supplemented with a review of Health Technology Assessment reports through the Centre for Reviews and Dissemination database. English language articles including any quantitative economic evaluation were included. The quality of each study was assessed using the British Medical Journal economic evaluation quality checklist. Data extracted included the main outcomes from each study, study methodologies, itemized costs, sensitivity ranges, biases, and delayed reoperation prevented with ITEE. When possible, a cost‐savings per ITEE was calculated to facilitate comparison across studies and used to create a synthesis of the results. Results: Seven studies met the inclusion criteria; of these, five were included in the synthesis of results. The cost‐savings per ITEE ranged from $194 to $4910 with a mean of $1930 (95%CI: $845 to $3015) (2015 USD). Prevented delayed reoperation rates using ITEE ranged from 2.8% to 10%. Earlier studies were of poorer quality (scores 8–17) and more recent studies were of higher quality (scores 22–25). Methodologies used were either retrospective chart reviews (57%) or prospective observational studies (43%) with a range of approaches to estimate costs. Conclusion: ITEE for pediatric cardiac surgery is effective and cost‐saving. This is a validation of the current practice patterns. These finding may influence the expansion of the use of this technology. Abstract :